L'accès à l'écriture à l'école maternelle : la dictée à l'adulte, un dispositif en question - Frédérique Adeline (Recherches en Éducation)
The article tries to show how a clinical observation of teaching practices addresses, maybe differently, the question of what can be at stake for teachers and pupils when it comes to writing at nursery school, by analyzing the specific te aching device that is « dictation to adult ». Drawing on the example of a session carried out by teacher called Eliane, we will find out that her « Well, let’s write it now! » is far from being obvious, from teachers’ and pupils’ point of view alike.